African spirituality that shapes the concept of Ubuntu - MJS Masango (Verbum et Ecclesia, 2006)
Nolan(1982:7) shares an interesting concept of spirituality. He says: The Spiritual life is the whole of ones life insofar as it is motivated and determined by the Holy Spirit, the spirit of Jesus. This kind of spirituality shapes persons in such a way that they grow into the concept of Ubuntu (humanness). In other words, an integrated spirituality is a spirituality in which who we are, and what we do are intimately related. The process of an African spiritualist is also developed within the village. Mbiti reminds us that: It takes a whole village to raise a child (Mbiti 1977:23). In short, relationship is part of development of African spirituality. This article further explores on how elders within the village become leaders, and towards the end of their life journey, they becomes teachers and good ancestors, especially to younger generation. It is important to note that those who are good (while iving) and are able to pass their knowledge and wisdom to others become good ancestors when they die...